Manufacturing method for rare earth magnets

JP2026166847APending Publication Date: 2026-10-14HONDA MOTOR CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2025060064
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0012】 以上の態様によれば、過電流損失が低減された希土類磁石を製造する希土類磁石の製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026166847000001_ABST
    Figure 2026166847000001_ABST
Patent Text Reader

Abstract

To provide a method for manufacturing rare earth magnets that produce rare earth magnets with reduced overcurrent loss. [Solution] A method for producing a rare earth magnet 1 from a magnetic powder granule 14 comprising stacked flake-shaped rare earth magnetic powder 11 and a binder compound that binds a plurality of rare earth magnetic powders 11, wherein the binder compound has thermal decomposition properties, decomposing at a thermal decomposition temperature lower than the melting point of the rare earth magnetic powder 11, and comprises (D) a binder removal step of heating the magnetic powder granule 14 to a temperature above the thermal decomposition temperature to thermally decompose the binder compound and obtain a degreased magnetic powder granule 15 by removing the binder compound from the magnetic powder granule 14, and (F) a hot plastic deformation step of performing hot plastic deformation on the degreased magnetic powder granule 15 obtained in (D) a binder removal step to obtain a rare earth magnet 1.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing a rare earth magnet.

Background Art

[0002] In recent years, efforts toward realizing a low-carbon society or a decarbonized society have intensified, and research and development on electrification technologies have been carried out in vehicles as well, in order to reduce CO2 emissions and improve energy efficiency. One of the methods for improving energy efficiency is to improve the efficiency of motors used as power sources. In order to improve motor efficiency, rare earth magnets have been widely used in recent years. And there is a demand for improving the magnetic properties of rare earth magnets. Since rare earth magnets are metallic magnets with low electrical resistivity, they have the problem that eddy current loss tends to increase. Accordingly, there are techniques for reducing overcurrent loss in rare earth magnets.

[0003] Patent Document 1 discloses a rare earth magnet capable of reducing eddy current loss, which has rare earth magnet powder covered with a film-like coating layer containing a rare earth oxide. Between the particles of the magnet powder coated with the rare earth oxide, a binding portion containing rare earth oxide particles is interposed. The rare earth magnet is produced by subjecting a mixture of rare earth magnet powder coated with a rare earth oxide and a rare earth oxide to high-temperature pressure molding.

[0004] Patent Document 2 discloses a method for producing a rare earth magnet, in which for the purpose of increasing the electrical resistivity of a rare earth magnet, magnet powder composed of an alloy mainly composed of an Nd2Fe14B compound is mixed with one or two or more insulating compounds selected from oxides such as CaO, nitrides such as BN, or fluorides such as CaF2, and the mixture is subjected to hot plastic working to obtain an anisotropic magnet material.

[0005] Patent Document 3 discloses a first method for manufacturing rare earth magnets, comprising the steps of: preparing isotropic quenched powder such as Nd-Fe-B magnet powder; mixing the isotropic quenched powder with a predetermined compound that will form an insulating layer; cold forming (pre-forming) the mixture; hot forming (densifying) the cold-formed body; and hot plastic working (anisotropizing). It is stated that the magnets manufactured by this method have a structure in which Nd-Fe-B quenched powder with a long side of 100 to 400 μm and a thickness of 20 to 40 μm is generally stacked on top of each other via compound powder. [Prior art documents] [Patent Documents]

[0006] [Patent Document 1] Patent No. 4784173 [Patent Document 2] Japanese Patent Publication No. 2003-22905 [Patent Document 2] Japanese Patent Publication No. 2010-27852 [Overview of the project] [Problems that the invention aims to solve]

[0007] The rare earth magnet described in Patent Document 1 uses an insulator made of dysprosium oxide (Dy2O3) as the rare earth oxide. Since dysprosium oxide is hygroscopic, the magnetic properties of the rare earth magnet may be reduced by water adsorbed on the dysprosium oxide. In the method for manufacturing a rare earth magnet described in Patent Document 2, in the mixing step in which Nd-Fe-B magnet powder and an insulating compound are mixed, the magnet powder is pulverized and excessively subdivided, increasing the specific surface area of ​​the magnet powder and making it more susceptible to oxidation. As a result, the rare earth magnet may be oxidized, which may reduce the magnetic flux density of the rare earth magnet.

[0008] In the rare earth magnet manufacturing method described in Patent Document 3, compound A, which is at least one selected from the group consisting of fluorides, oxides, and inorganic salts of heavy rare earth elements, and compound B, which is a hydride of an alkaline earth metal, are reacted during the hot forming and heat treatment processes. However, side reactions such as oxidation of the magnet or improper reaction between compound A and compound B may reduce the magnetic properties of the manufactured rare earth magnet. Therefore, there is a need for rare earth magnet materials with reduced overcurrent loss, and for rare earth magnets with reduced overcurrent loss.

[0009] In view of the above background, the present invention aims to provide a method for manufacturing rare-earth magnets with reduced overcurrent loss, and thereby contribute to improving energy efficiency. [Means for solving the problem]

[0010] To solve the above problems, one aspect of the present invention provides a method for producing a rare earth magnet from a magnetic powder granule comprising stacked flake-shaped rare earth magnetic powder and a binder compound that binds a plurality of the rare earth magnetic powders, wherein the binder compound has thermal decomposition properties such that it decomposes at a thermal decomposition temperature lower than the melting point of the rare earth magnetic powder, and the method includes a binder removal step of heating the magnetic powder granules to a temperature above the thermal decomposition temperature to thermally decompose the binder compound and obtain a degreased magnetic powder granule by removing the binder compound from the magnetic powder granule; and a hot plastic deformation step of performing hot plastic deformation on the degreased magnetic powder granule obtained in the binder removal step to obtain a rare earth magnet.

[0011] According to this embodiment, a method for manufacturing rare earth magnets can be provided for producing rare earth magnets with reduced overcurrent loss. [Effects of the Invention]

[0012] According to the above embodiments, it is possible to provide a method for manufacturing rare earth magnets that produce rare earth magnets with reduced overcurrent loss. [Brief explanation of the drawing]

[0013] [Figure 1] Schematic cross-sectional view of the rare-earth magnet according to the embodiment [Figure 2] Diagram showing the method for manufacturing a rare-earth magnet according to the embodiment [Figure 3] Schematic diagram of a tumbling flow apparatus [Figure 4] Graph showing the difference in properties of rare-earth magnet 1 due to different methods of heating magnetic powder particles in the binder removal step [Figure 5] Schematic diagram showing a state where magnetic powder particles are being heated [Mode for Carrying Out the Invention]

[0014] Hereinafter, the rare-earth magnet 1 according to the embodiment of the present invention will be described in detail with reference to the drawings. In the following description, the numerical range indicated by "XX to XX" means "not less than XX and not more than XX" unless otherwise specified.

[0015] <Structure of Rare-Earth Magnet 1> Figure 1 is a schematic cross-sectional view of the rare-earth magnet 1 of the embodiment. As shown in Figure 1, the rare-earth magnet 1 includes a plurality of insulating magnet powder particles 2 arranged in layers. The insulating magnet powder particle 2 has a plurality of flaky (flake-shaped) rare-earth magnet powders 3 stacked, and an insulating layer 4 formed on the surface layer of the insulating magnet powder particle 2 and having insulating properties. The insulating layer 4 covers the outer peripheral surface of the stacked rare-earth magnet powders 3.

[0016] The rare-earth magnet powder 3 is preferably a flaky neodymium magnet (Nd-Fe-B based magnet, precisely Nd2Fe 14 B).

[0017] The insulating layer 4 includes a plurality of fluoride nanoparticles 4A made of fluoride, which are particles made of calcium fluoride (CaF2). Calcium fluoride (CaF2) has a melting point higher than that of the rare-earth magnet powder 3 and low reactivity with the rare-earth magnet powder 3. The particle size of the fluoride nanoparticles 4A is preferably 1 to 100 nm.

[0018] The fluoride nanoparticles 4A may be particles composed of an insulating inorganic fluorine compound. The fluoride nanoparticles 4A preferably have a melting point higher than that of the rare earth magnet powder 3 and low reactivity with the rare earth magnet powder 3. Since the melting point is higher than that of the rare earth magnet powder 3 and the reactivity with the rare earth magnet powder 3 is low, the fluoride nanoparticles 4A are preferably nanoparticles composed of an alkali metal fluoride such as lithium fluoride, or nanoparticles composed of an alkaline earth metal fluoride such as magnesium fluoride, barium fluoride, and strontium fluoride. The insulating layer 4 may include, as the fluoride nanoparticles 4A, a plurality of nanoparticles composed of an alkali metal fluoride and a plurality of nanoparticles composed of an alkaline earth metal fluoride. The insulating layer 4 may also include, as the fluoride nanoparticles 4A, nanoparticles containing an alkali metal fluoride and an alkaline earth metal fluoride.

[0019] As will be described later, in the manufacturing process of the rare earth magnet 1 (the hot plastic working step (F) in FIG. 3), the rare earth magnet powder 3 is heated while being pressurized in the direction (first direction) orthogonal to the main surface. As a result, the crystal grains in the magnet are short in the first direction (compression direction) and long in the orthogonal direction (the direction in which the main surface extends) orthogonal to the first direction. The rare earth magnet 1 is magnetized in the first direction (compression direction). The squareness ratio of the rare earth magnet 1 is enhanced by the crystal grains of the rare earth magnet 1 being oriented as described above and magnetized as described above.

[0020] Further, as shown in FIG. 1, the rare earth magnet 1 is an aggregate of insulated magnet powder particles 2 each having an insulating layer 4 on the surface layer. Since the rare earth magnet 1 is composed of a plurality of insulated magnet powder particles 2 separated from each other by the insulating layer 4, the electrical resistivity is increased. Thereby, the eddy current loss of the rare earth magnet 1 is reduced. Therefore, the rare earth magnet 1 has a favorable squareness ratio and reduced eddy current loss.

[0021] <Method for Manufacturing Rare Earth Magnet 1> Figure 2 is a diagram showing a method for manufacturing a rare earth magnet 1. As shown in Figure 2, the method for manufacturing a rare earth magnet 1 includes (A) a magnetic powder manufacturing step for manufacturing rare earth magnetic powder 11, (B) a binding step for obtaining a magnetic powder precursor 12 by binding the rare earth magnetic powder 11 in layers, (C) an insulating layer formation step for obtaining magnetic powder 14 by forming an insulating layer 13 on the magnetic powder precursor 12, (D) a binder removal step for obtaining degreased magnetic powder 15 by removing binder compounds contained in the magnetic powder 14 by thermal decomposition, (E) a primary molding step for obtaining a primary molded body 16 by primary molding of the degreased magnetic powder 15, and (F) a hot plastic deformation step for obtaining a rare earth magnet 1 by performing hot plastic deformation on the primary molded body 16.

[0022] (A) The magnetic powder manufacturing process is a process for manufacturing rare earth magnetic powder 11 in the form of flakes of a predetermined size. (A) The melt spinning method is preferably used in the magnetic powder manufacturing process. As shown in Figure 2(A), the melt spinning method is a method for obtaining thin plate-shaped magnets by heating rare earth magnets to a liquid state, spraying them onto a roll, and then cooling them. The composition of the rare earth magnets to be liquefied is the same as the composition of the rare earth magnet powder 3. Furthermore, the thin plate-shaped magnets are crushed to obtain minute magnet fragments 17. Then, the rare earth magnetic powder 11 is classified from the minute magnet fragments 17 to obtain the rare earth magnetic powder 11. Note that the melt spinning method is not required in the magnetic powder manufacturing process. (A) The magnetic powder manufacturing process may also be a process for obtaining rare earth magnetic powder 11 by crushing thin plate-shaped rare earth magnets.

[0023] The rare earth magnetic powder 11 is a flaky neodymium magnet (Nd-Fe-B type magnet, more precisely Nd2Fe 14 B) is preferable. Anisotropy is the property that the crystal orientations (easy magnetization axis, c-axis) are aligned in a specific direction. Isotropy, on the other hand, is the property that the crystal orientations are not aligned in a specific direction.

[0024] The rare earth magnetic powder 11 becomes more brittle as it becomes thinner. The lower limit of the major axis of the rare earth magnetic powder 11 is 300 μm, and the average thickness of the rare earth magnetic powder 11 is preferably 10 μm to 30 μm. Furthermore, an average thickness of 20 μm is preferable.

[0025] The rare earth magnetic powder 11 is flaky and has a pair of main surfaces 11A. The main surface 11A is the largest pair of flat surfaces facing opposite directions. The rare earth magnetic powder 11 may have an aspect ratio of approximately 1 (for example, 0.11 to 1.0) when viewed from a direction perpendicular to the main surface 11A. The aspect ratio is the size of the minor axis b (minor axis diameter) relative to the major axis a (major axis diameter) of the particle (aspect ratio = minor axis b / major axis a). Here, the major axis a (major axis diameter) means the maximum Ferret diameter, and the minor axis b (minor axis diameter) means the minimum Ferret diameter. The measurement method for the major and minor axes conforms to the provisions of JIS Z8890:2017 "Evaluation of Particle Special Zone Characteristics of Powders".

[0026] (B) The binding step is a step in which multiple rare earth magnetic powders 11 are bound in layers with a binder compound to obtain a magnetic powder precursor 12. (B) In the binding step, a rolling flow device 20 (see Figure 3) may be used to spray a binder compound solution onto the rolling flow of rare earth magnetic powders 11, thereby binding multiple rare earth magnetic powders 11 in layers with the binder compound.

[0027] The binder compound solution is, for example, a solution containing 4 wt% of the binder compound. The binder compound is preferably an acrylic polymer with a weight-average molecular weight greater than 100,000 and less than or equal to 300,000. The acrylic polymer has thermal decomposition properties, meaning it decomposes at a temperature lower than the melting point of the rare-earth magnetic powder 7.

[0028] The binder compound can be any compound capable of binding the rare earth magnetic powder 7. The binder compound does not need to have a weight-average molecular weight greater than 100,000, nor does it need to have a weight-average molecular weight less than 300,000. Furthermore, the binder compound does not need to be an acrylic polymer. The binder compound is preferably a resin. Also, the binder compound does not need to be thermally decomposable, meaning it does not decompose at a temperature lower than the melting point of the rare earth magnetic powder 7.

[0029] The solvent for the binder compound solution is preferably 2-propanol (also known as "isopropyl alcohol" or "IPA"). The solvent for the binder compound solution does not have to be 2-propanol. The solvent for the binder compound solution is preferably an alcohol. To allow for easy evaporation after the rare earth magnetic powder 11 has been bonded in layers, the solvent for the binder compound solution is preferably a solvent that evaporates easily at room temperature.

[0030] Figure 3 is a schematic diagram of the rolling fluidizer 20. As shown in Figure 3, the rolling fluidizer 20 comprises a main body case 22 having a fluidized bed 21 inside for rolling and fluidizing rare earth magnetic powder 11, a rotatable blade rotor 23 defining the bottom of the fluidized bed 21, a spray nozzle 24 provided on the side of the main body case 22, and a blower (not shown) that sends a swirling flow of air into the fluidized bed 21 through the gap between the outer circumference of the blade rotor 23 and the main body case 22. The blade rotor 23 has a conical portion 23A that protrudes upward in the center and stirring blades 23B that protrude upward and extend radially. The spray nozzle 24 is attached to the main body case 22 so that it can spray a binder compound solution toward the bottom of the fluidized bed 21.

[0031] (B) In the binding process, the rare earth magnetic powder 11 is placed in the fluidized bed 21. The blade rotor 23 is rotated, and a swirling flow of air in the fluidized bed 21 is generated by the blower. This causes the rare earth magnetic powder 11 in the fluidized bed 21 to roll and flow. In this state, the binder compound solution is sprayed onto the rolling rare earth magnetic powder 11 from the spray nozzle 24. Here, in order to properly bind the rare earth magnetic powder 11, it is preferable that the binder compound solution be sprayed at a rate of 5 g / min to 30 g / min per 1 kg of rolling rare earth magnetic powder 11.

[0032] The rare earth magnetic powder 11 is bound by a sprayed binder compound solution. Here, the binder compound solution binds between the main surfaces 11A of adjacent rare earth magnetic powders 11. The solvent (IPA) evaporates from the binder compound solution that binds the rare earth magnetic powder 11. Then, a magnetic powder precursor 12 is obtained, in which multiple rare earth magnetic powders 11 are bound in layers by the binder compound. Here, binding in layers means that multiple rare earth magnetic powders 11 are bound with their main surfaces 11A facing the same direction. The magnetic powder precursor 12 is a stacked, flaky form of multiple rare earth magnetic powders 11. "Stacked, flaky form of rare earth magnetic powder 11" means multiple rare earth magnetic powders 11 that are stacked with their main surfaces 11A facing the same direction.

[0033] In the magnetic powder precursor 12, the binder compound solution that binds the rare earth magnetic powder 11 is dry. The magnetic powder precursor 12 preferably contains 0.5 to 2.5 wt% of the binder compound. The concentration of the binder compound in the binder compound solution and the amount of the binder compound solution injected are set so that the magnetic powder precursor 12 contains 0.5 to 2.5 wt% of the binder compound. In order for the rare earth magnet 1 produced from the magnetic powder precursor 12 to have suitable magnetic properties, the thickness of the magnetic powder precursor 12 in the stacking direction is preferably 0.15 mm or more and 1 mm or less.

[0034] As shown in Figure 2, (C) the insulating layer formation step is a step of forming an insulating layer 13 having insulating properties on the surface of the magnetic powder precursor 12 to obtain magnetic powder 14. The magnetic powder 14 is a powder obtained by forming an insulating layer 13 on the magnetic powder precursor 12. In (C) the insulating layer formation step, a nanoparticle dispersion containing a plurality of fluoride nanoparticles 4A is sprayed onto the magnetic powder precursor 12, which is being rolled and flowed using a rolling flow device 20, to form an insulating layer 13 on the surface of the magnetic powder precursor 12.

[0035] As described above, the fluoride nanoparticles 4A are particles made of calcium fluoride (CaF2). The particle size of the fluoride nanoparticles 4A is preferably 1 to 100 nm. The fluoride nanoparticles 4A may be particles made of an inorganic fluorine compound having insulating properties. The fluoride nanoparticles 4A should have a melting point higher than the melting point of the rare earth magnet powder 3 and have poor reactivity with the rare earth magnet powder 3. The fluoride nanoparticles 4A are preferably nanoparticles made of alkali metal fluorides such as lithium fluoride, or nanoparticles made of alkaline earth metal fluorides such as magnesium fluoride, barium fluoride, or strontium fluoride. The insulating layer 4 may include a plurality of nanoparticles made of alkali metal fluorides and a plurality of nanoparticles made of alkaline earth metal fluorides as the fluoride nanoparticles 4A. The insulating layer 4 may also include nanoparticles containing alkali metal fluorides and alkaline earth metal fluorides as the fluoride nanoparticles 4A.

[0036] The nanoparticle dispersion contains, for example, 4 wt% of fluoride nanoparticles 4A and 2.5 wt% of a binder compound. As a result, the insulating layer 13 formed by drying the nanoparticle dispersion contains 38 wt% of the binder compound and 62 wt% of fluoride nanoparticles 4A.

[0037] The solvent for the nanoparticle dispersion is preferably 2-propanol (IPA). The binder compound is a compound that can bind the fluoride nanoparticles 4A, and is preferably the same compound as the binder compound used in the binding step (B). The fluoride nanoparticles 4A are dispersed in the nanoparticle dispersion. The concentration of fluoride nanoparticles 4A, the concentration of the binder compound, and the solvent in the nanoparticle dispersion may be changed.

[0038] (C) In the insulating layer formation process, as shown in Figure 3, the magnetic powder precursor 12 is placed in the fluidized bed 21 of the rolling fluidizer 20. The blade rotor 23 is rotated and a swirling flow of air in the fluidized bed 21 is generated by the blower. As a result, the magnetic powder precursor 12 in the fluidized bed 21 rolls and flows. In this state, a nanoparticle dispersion is sprayed onto the rolling magnetic powder precursor 12 from the spray nozzle 24. The sprayed nanoparticle dispersion adheres to the surface of the magnetic powder precursor 12 and dries. As a result, an insulating layer 13 is formed on the surface of the magnetic powder precursor 12, and magnetic powder 14 is obtained.

[0039] The insulating layer 13 formed as described above preferably contains a plurality of fluoride nanoparticles 4A having a particle size of 1 to 100 nm and a binder compound that binds the plurality of fluoride nanoparticles 4A together in an amount of 20 wt% or more.

[0040] (D) The binder removal step is a step in which the magnetic powder 14 is heated to a temperature above the thermal decomposition temperature of the binder compound to thermally decompose the binder compound and obtain degreased magnetic powder 15 by removing the binder compound from the magnetic powder 14.

[0041] (D) In ​​the binder removal step, the magnetic powder 14 may be heated in the mold of the hot press machine. As shown in Figure 2(D), the mold 30 of the hot press machine has a cylindrical mold body 31 and an upper mold 32 and a lower mold 33 that can apply a compressive force in a first direction to the object inside the mold body 31. In Figure 2, the first direction is the vertical direction, but the first direction may be a direction other than the vertical direction.

[0042] (D) In ​​the binder removal process, the magnetic powder 14 placed in the mold body 31 of the mold 30 is heated to a temperature above the thermal decomposition temperature of the binder compound (e.g., 300°C to 400°C) for a predetermined time (e.g., 2 to 4 hours) in a reduced pressure environment or in an inert gas stream, without being pressurized by the mold 30 (upper mold 32 and lower mold 33). The inert gas is a gas that has poor reactivity with the rare earth magnetic powder 11. The inert gas is preferably a noble gas, for example. The inert gas is preferably helium gas. Air may be used instead of the inert gas.

[0043] The products of the thermal decomposition of the binder compound are discharged from the mold 30. The binder compound is preferably an acrylic polymer (polymethyl methacrylate) with a weight-average molecular weight greater than 100,000 and less than or equal to 300,000. The acrylic polymer is thermally decomposed into the monomer methyl methacrylate. The decomposition products generated by the thermal decomposition of the binder compound volatilize and are discharged from the mold 30.

[0044] (D) When the magnetic powder granules 14 are heated under reduced pressure in the binder removal process, the mold body 31 (mold 30) is heated under reduced pressure while the magnetic powder granules 14 are heated. In this case, the decomposition products of the binder compound (for example, the monomer methyl methacrylate) become more volatile due to being in a reduced pressure environment and are more easily discharged outside the mold body 31 (mold 30). In addition, the decomposition products of the binder compound are less likely to accumulate around the magnetic powder granules 14, and their reaction with the rare earth magnetic powder 11 and subsequent degradation of the rare earth magnetic powder 11 is suppressed.

[0045] When heating magnetic powder granules 14 in an inert gas stream, the magnetic powder granules 14 are heated while the inert gas is flowed inside the mold body 31 (mold 30). This makes it easier for decomposition products of the binder compound (e.g., methyl methacrylate monomer) to be discharged outside the mold body 31 (mold 30) by the inert gas stream. In addition, the decomposition products of the binder compound are less likely to accumulate around the magnetic powder granules 14, and their reaction with the rare earth magnetic powder 11, which degrades the rare earth magnetic powder 11, is suppressed. It is preferable that the inert gas be heated to a temperature above the thermal decomposition temperature of the binder compound before being introduced into the mold 30. This promotes the thermal decomposition of the binder compound because it is heated by the inert gas.

[0046] (E) The primary molding step is a step of pressurizing the degreased magnetic powder granules 15 to obtain a primary molded body 16. (E) A mold 30 may be used in the primary molding step. (E) The primary molding step is a step of primary molding the degreased magnetic powder granules 15, which have had the binder compound removed from the magnetic powder granules 14, to obtain a primary molded body 16. (E) The primary molding step may be considered as a type of step of primary molding a plurality of magnetic powder granules 14 obtained in the (C) insulating layer forming step to obtain a primary molded body 16 in which the plurality of magnetic powder granules 14 have been primary molded.

[0047] (E) The primary molding step may be a step in which the degreased magnetic powder granules 15 are heated to a predetermined temperature in a mold 30 and a predetermined pressure is applied for a predetermined time to perform hot press molding (primary molding). Here, hot press molding may be performed at a mold temperature of 600°C to 700°C, preferably around 640°C. When the degreased magnetic powder granules 15 are pressurized in the mold 30, the multiple degreased magnetic powder granules 15 are oriented so that the main surface 11A of the rare earth magnetic powder 11 contained in the degreased magnetic powder granules 15 faces a first direction, and they are stacked on top of each other in a direction perpendicular to the main surface 11A (first direction). Therefore, by hot press molding, the multiple degreased magnetic powder granules 15 are compressed and deformed in a state where they are stacked on top of each other in a direction perpendicular to the main surface (main surface 11A of the rare earth magnetic powder 11) (first direction).

[0048] (F) The hot plastic deformation process is a process of obtaining a rare earth magnet 1 by performing hot plastic deformation on the primary molded body 16 obtained in the (E) primary molding process. Since the primary molded body 16 contains multiple degreased magnetic powder particles 15, (F) the hot plastic deformation process can be said to be a process of obtaining a rare earth magnet 1 by performing hot plastic deformation on the degreased magnetic powder particles 15 obtained in the (D) binder removal process. In the (F) hot plastic deformation process, the primary molded body 16 is heated and pressurized to a temperature at which some of the crystal grains of the rare earth magnetic powder 11 undergo a phase change to the liquid phase (the melting point of the rare earth magnetic powder 11, for example, around 850°C), thereby causing the primary molded body 16 to plastically deform.

[0049] (F) The hot plastic deformation process is carried out using a secondary molding die 40. The secondary molding die 40 has an upper press mold 41 and a lower press mold 42 that are arranged opposite each other. The primary molded body 16 is placed in the secondary molding die 40 such that the multiple degreased magnetic powder particles 15 contained in the primary molded body 16 are pressed in a direction perpendicular to the main surface 11A (first direction). During the plastic deformation process of the primary molded body 16, the c-axis direction (easy magnetization direction) of the crystal grains of the rare earth magnetic powder 11 contained in the primary molded body 16 is oriented in a direction parallel to the first direction (compression direction), so that magnetic anisotropy (uniaxial anisotropy) is exhibited in the primary molded body 16 during the plastic deformation process. The rare earth magnetic powder 3 contained in the rare earth magnet 1 is formed when the rare earth magnetic powder 11 is plastically deformed and its crystal grains are oriented in the first direction (compression direction). The rare earth magnet 1 (see Figure 1) obtained in the hot composition processing process is magnetized in the direction in which this magnetic anisotropy manifests (first direction).

[0050] (F) In the hot plastic deformation process, the degreased magnetic powder 15 is heated while being pressurized in a direction perpendicular to the main surface of the degreased magnetic powder 15 (first direction). As a result, the crystal grains in the magnet are shorter in the first direction (compression direction) and longer in the orthogonal direction perpendicular to the first direction (direction in which the main surface extends). In addition, the rare earth magnet 1 is magnetized in the first direction (compression direction). The rare earth magnet 1 has multiple stacked flake-like rare earth magnet powders 3, and the crystal grains are oriented as described above, and the magnetization is performed as described above, thereby increasing the angularity ratio of the rare earth magnet 1.

[0051] Furthermore, as shown in Figure 1, the rare earth magnet 1 is an aggregate of insulating magnet powders 2 having an insulating layer 4 on its surface, and the insulating layer 4 increases its electrical resistivity. This reduces the overcurrent loss of the rare earth magnet 1. Therefore, the rare earth magnet 1 has a suitable square aspect ratio and its overcurrent loss can be reduced.

[0052] Next, the effects of the rare earth magnet 1 manufactured in this manner and its manufacturing method will be explained.

[0053] The method for manufacturing the rare earth magnet 1 includes (D) a binder removal step in which the binder compound is thermally decomposed to obtain a degreased magnetic powder granule 15 by removing the binder compound from the magnetic powder granule 14, and (F) a hot plastic deformation step in which the degreased magnetic powder granule 15 obtained in step (D) is subjected to hot plastic deformation to obtain the rare earth magnet 1. The binder compound is thermally decomposable, decomposing at a thermal decomposition temperature lower than the melting point of the rare earth magnetic powder 11.

[0054] (D) In ​​the binder removal process, the binder compound is removed from the magnetic powder granules 14, so the volume of the insulating layer 13 decreases. In the manufacturing method of the rare earth magnet 1, (F) the binder compound is removed before hot plastic working. As a result, the binder compound is thermally decomposed during the process of (F) hot plastic working, which suppresses the decrease in magnetic properties such as residual magnetic flux density caused by 1 and 2 below. 1. Degradation of magnetic properties due to the reaction of decomposition products of the binder compound (e.g., methyl methacrylate monomer) with the rare earth magnetic powder 11. 2. The presence of a binder compound creates a void, leading to a decrease in the density of the rare-earth magnet and a reduction in its magnetic properties. Therefore, a rare-earth magnet 1 with desirable magnetic properties can be manufactured from magnetic powder granules 14.

[0055] (D) After removing the binder compound in the binder removal process, (E) the primary molding process is performed, followed by (F) the hot plastic working process. Here, since the binder compound is removed before the (E) primary molding process, deformation of the primary molded body 16 due to thermal decomposition of the binder compound during the (E) primary molding process is suppressed. In addition, the shape of the rare earth magnet 1 is determined by the (E) primary molding process and the (F) hot plastic working process, and the c-axis direction (easy magnetization direction) of the crystal grains is oriented in a direction parallel to the first direction (compression direction). Therefore, deformation of the rare earth magnet 1 due to thermal decomposition of the binder compound can be suppressed.

[0056] Furthermore, the magnetic powder granules 14 that are not arranged in layers before the primary molding process (E) have better permeability than the primary molded body 16 in which the magnetic powder granules 14 are arranged in layers. (D) In ​​the binder removal process, the binder compound is removed by thermal decomposition while the magnetic powder granules 14 have good permeability, so the binder compound can be removed quickly and reliably.

[0057] (D) In ​​the binder removal process, the magnetic powder 14 is heated to a temperature above its thermal decomposition temperature under no pressure and in a reduced pressure environment.

[0058] Figure 4 is a graph showing the difference in properties of the rare earth magnet 1 due to the difference in the method of heating the magnetic powder granules 14 in the (D) binder removal process. Figure 4A is a graph showing the difference in carbon concentration of the rare earth magnet 1 due to the difference in the method of heating the magnetic powder granules 14 in the (D) binder removal process. Figure 4B is a graph showing the difference in coercivity iHC of the rare earth magnet 1 due to the difference in the method of heating the magnetic powder granules 14 in the (D) binder removal process.

[0059] Figure 5 is a diagram schematically showing a state in which magnetic powder granules 14 are being heated. Figure 5A is a diagram schematically showing a state in which the magnetic powder granules 14 are heated without being pressurized in a space enclosed by the mold body 31, the upper mold 32 and the lower mold 33 of the mold 30. Figure 5B is a diagram schematically showing a state in which the magnetic powder granules 14 are heated without being pressurized in an open space within the mold 30.

[0060] In Figure 4A and Figure 4B, A, B and C have the following meanings. A is a rare earth magnet produced by performing (D) a binder removal step in which the magnetic powder granules 14 are heated (see Figure 5A) in a closed space within the mold 30 to remove the binder compound, followed by (E) a primary forming step and (F) a hot plastic working step. B is a rare earth magnet produced by performing (D) a binder removal step in which the magnetic powder granules 14 are heated in an open space within the mold 30 (see Figure 5B) to remove the binder compound, followed by (E) a primary forming step and (F) a hot plastic working step. C is a rare earth magnet 1 produced by performing (D) a binder removal step in which the magnetic powder granules 14 are heated under reduced pressure in an open space within the mold 30 (see Figure 6B) to remove the binder compound, followed by (E) a primary forming step and (F) a hot plastic working step.

[0061] As shown in Figure 4A, the relationship "carbon concentration of A > carbon concentration of B > carbon concentration of C" is satisfied. The carbon contained in the rare earth magnet is considered to originate from the binder compound that has not been thermally decomposed in the rare earth magnet. For this reason, it is considered that the lower the carbon content in the rare earth magnet, the smaller the amount of the binder compound that has not been thermally decomposed in the rare earth magnet. Accordingly, the ease of thermal decomposition of the binder compound follows the relationship "heating the magnetic powder granules 14 in A closed space < heating the magnetic powder granules 14 in B open space < heating the magnetic powder granules 14 in C open space".

[0062] As shown in Figure 4B, the relationship is "coercivity of A < coercivity of B < coercivity of C". It is considered that the smaller the amount of undecomposed binder compound in the rare earth magnet, the higher the coercivity of the rare earth magnet. Therefore, the coercivity of the rare earth magnet satisfies "A heating the magnetic powder and granule 14 in a closed space < B heating the magnetic powder and granule 14 in an open space < C heating the magnetic powder and granule 14 in an open space".

[0063] As described above, Figure 4A and Figure 4B show that in the binder removal step, the magnetic powder and granule 14 is heated to a temperature equal to or higher than the thermal decomposition temperature in a non-pressurized state under a reduced pressure environment, whereby the amount of undecomposed binder compound remaining in the rare earth magnet 1 produced from the magnetic powder and granule 14 can be reduced, and the coercivity of the rare earth magnet can be improved. Therefore, in the binder removal step, the magnetic powder and granule 14 is heated to a temperature equal to or higher than the thermal decomposition temperature in a non-pressurized state under a reduced pressure environment, so that the amount of undecomposed binder compound remaining in the rare earth magnet 1 produced from the magnetic powder and granule 14 can be reduced, and the coercivity of the rare earth magnet 1 produced from the magnetic powder and granule 14 can be improved.

[0064] (D) In the binder removal step, the magnetic powder and granule 14 is heated to a temperature equal to or higher than the thermal decomposition temperature in a non-pressurized state in an inert gas stream. Thereby, the binder compound in the magnetic powder and granule 14 can be thermally decomposed more rapidly and reliably removed. Therefore, the amount of undecomposed binder compound remaining in the rare earth magnet 1 produced from the magnetic powder and granule 14 can be reduced.

[0065] (D) In the binder removal step, the magnetic powder and granule 14 is heated to a temperature equal to or higher than the thermal decomposition temperature in a non-pressurized state in an inert gas stream at a temperature equal to or higher than the thermal decomposition temperature. The inert gas stream promotes the thermal decomposition of the binder compound, whereby the binder compound in the magnetic powder and granule 14 can be thermally decomposed more rapidly and reliably removed.

[0066] The magnetic powder granules 14 include an insulating layer 13 formed on its surface. This makes it easy to manufacture a rare earth magnet 1 with relatively high electrical resistivity using the magnetic powder granules 14.

[0067] The weight-average molecular weight of the binder compound contained in the insulating layer 13 is between 100,000 and 300,000. The higher the weight-average molecular weight of the binder compound, the stronger the adhesive force and the less soluble it becomes in the solvent. By having a weight-average molecular weight of 100,000 and 300,000, the adhesive force of the binder compound is sufficiently high, and it becomes sufficiently soluble in the solvent. This makes it possible to form an insulating layer 13 suitable for the magnetic powder granules 14. As a result, the electrical resistivity of the rare earth magnet 1 produced from the magnetic powder granules 14 can be reliably increased, and the overcurrent loss of the rare earth magnet 1 can be reliably reduced.

[0068] The binder compound is an acrylic polymer. This makes it easier to remove the binder compound by thermal decomposition during the process of manufacturing the rare earth magnet 1 from the magnetic powder granules 14, and also reduces the amount of undecomposed binder compound remaining in the rare earth magnet 1.

[0069] This concludes the description of specific embodiments, but the present invention is not limited to the above embodiments and can be broadly modified and implemented. For example, the solvent for the binder compound solution and the nanoparticle dispersion does not have to be IPA, but may be an alcohol that is liquid at room temperature, such as 1-propanol or butanol.

[0070] The above embodiments may also be described as follows:

[0071] One embodiment is a method for producing a rare earth magnet 1 from a magnetic powder granule 14 comprising stacked flake-shaped rare earth magnetic powder 11 and a binder compound that binds a plurality of rare earth magnetic powders 11, wherein the binder compound has thermal decomposition properties, decomposing at a thermal decomposition temperature lower than the melting point of the rare earth magnetic powder 11, and the method includes (D) a binder removal step in which the magnetic powder granule 14 is heated to a temperature above the thermal decomposition temperature to thermally decompose the binder compound and obtain a degreased magnetic powder granule 15 from which the binder compound has been removed, and (F) a hot plastic deformation step in which the degreased magnetic powder granule 15 obtained in (D) a binder removal step is subjected to hot plastic deformation to obtain a rare earth magnet 1.

[0072] According to this embodiment, (F) during the process of hot plastic working, the binder compound is thermally decomposed, thereby suppressing the decrease in magnetic properties such as residual magnetic flux density due to the following 1 and 2. 1. Degradation of magnetic properties due to the reaction of decomposition products of the binder compound (e.g., methyl methacrylate monomer) with the rare earth magnetic powder 11. 2. The presence of a binder compound creates a void, leading to a decrease in the density of the rare-earth magnet and a reduction in its magnetic properties. Therefore, a rare-earth magnet 1 with desirable magnetic properties can be manufactured from magnetic powder granules 14.

[0073] In one embodiment of the manufacturing method for the rare earth magnet 1, after the (D) binder removal step and before the (F) hot plastic working step, a (E) primary molding step is performed in which a plurality of degreased magnetic powder particles 15 obtained in the (D) binder removal step are arranged in layers to obtain a primary molded body 16 in which the plurality of degreased magnetic powder particles 15 are primary molded, and in the (F) hot plastic working step, hot plastic working is performed on the primary molded body 16 obtained in the (E) primary molding step to obtain the rare earth magnet 1.

[0074] In this embodiment, deformation of the primary molded body 16 is suppressed by the thermal decomposition of the binder compound during the primary molding process (E). Therefore, deformation of the rare earth magnet 1 due to thermal decomposition of the binder compound can be suppressed. Furthermore, since the binder compound is removed by thermal decomposition while the magnetic powder granules 14 have good permeability, the binder compound can be removed quickly and reliably.

[0075] In one embodiment of the method for manufacturing a rare earth magnet 1, in the (D) binder removal step, the magnetic powder granules 14 are heated to a temperature above the thermal decomposition temperature under a reduced pressure environment without pressurization.

[0076] According to this embodiment, it is possible to reduce the amount of undecomposed binder compounds remaining in the rare earth magnet 1 manufactured from the magnetic powder granules 14, and to improve the coercivity of the rare earth magnet 1 manufactured from the magnetic powder granules 14.

[0077] In one embodiment of the method for manufacturing a rare earth magnet 1, in the (D) binder removal step, the magnetic powder granules 14 are heated to a temperature above the thermal decomposition temperature in an inert gas stream without pressurization.

[0078] According to this embodiment, the amount of undegraded binder compounds remaining in the rare earth magnet 1 manufactured from the magnetic powder granules 14 can be reduced.

[0079] In one embodiment of the method for manufacturing a rare earth magnet 1, in the (D) binder removal step, the magnetic powder granules 14 are heated to a temperature above the thermal decomposition temperature in an inert gas stream at a temperature above the thermal decomposition temperature without pressurization.

[0080] According to this embodiment, the amount of undegraded binder compounds remaining in the rare earth magnet 1 manufactured from the magnetic powder granules 14 can be reduced.

[0081] In one embodiment of the method for manufacturing a rare earth magnet, the magnetic powder granules 14 include an insulating layer 13 having insulating properties formed on its surface.

[0082] According to this embodiment, it becomes easier to manufacture a rare earth magnet 1 with relatively high electrical resistivity using magnetic powder granules 14.

[0083] According to this embodiment, it becomes easier to manufacture the magnetic powder 14.

[0084] In one embodiment of the method for manufacturing a rare earth magnet 1, the weight-average molecular weight of the binder compound is greater than 100,000 and less than or equal to 300,000.

[0085] According to this embodiment, an insulating layer 13 suitable for the magnetic powder granules 14 can be formed. As a result, the electrical resistivity of the rare earth magnet 1 manufactured from the magnetic powder granules 14 can be reliably increased, and the overcurrent loss of the rare earth magnet 1 can be reliably reduced.

[0086] In one embodiment of the method for manufacturing rare earth magnets, the binder compound is an acrylic polymer.

[0087] According to this embodiment, the binder compound can be easily removed by thermal decomposition during the process of manufacturing the rare earth magnet 1 from the magnetic powder granules 14, and the amount of undecomposed binder compound remaining in the rare earth magnet 1 can be reduced. [Explanation of Symbols]

[0088] 1: Rare earth magnets 4: Insulating layer 7: Rare earth magnetic powder 11: Rare earth magnetic powder 13: Insulating layer 14:Magnetic powder 15: Degreased magnetic powder 16: Primary molded body

Claims

1. A method for producing a rare earth magnet from magnetic powder granules comprising stacked flake-shaped rare earth magnetic powders and a binder compound that binds a plurality of the rare earth magnetic powders, The binder compound has thermal decomposition properties, such that it decomposes at a thermal decomposition temperature lower than the melting point of the rare earth magnetic powder. A binder removal step is performed to obtain degreased magnetic powder by heating the magnetic powder to a temperature above the thermal decomposition temperature to thermally decompose the binder compound and remove the binder compound from the magnetic powder. A method for producing a rare earth magnet, comprising: a hot plastic deformation step of the degreased magnetic powder obtained in the binder removal step to obtain a rare earth magnet.

2. After the binder removal step and before the hot plastic working step, a primary molding step is performed to obtain a primary molded body from which the multiple degreased magnetic powder particles obtained in the binder removal step have been primary molded. The method for manufacturing a rare earth magnet according to claim 1, wherein the hot plastic deformation step is performed by hot plastic deformation on the primary molded body obtained in the primary molding step to obtain a rare earth magnet.

3. The method for manufacturing a rare earth magnet according to claim 1, wherein in the binder removal step, the magnetic powder is heated to a temperature above the thermal decomposition temperature under a reduced pressure environment without pressurization.

4. The method for manufacturing a rare earth magnet according to claim 1, wherein in the binder removal step, the magnetic powder is heated to a temperature above the thermal decomposition temperature in an airflow of an inert gas without pressurization.

5. The method for manufacturing a rare earth magnet according to claim 4, wherein in the binder removal step, the magnetic powder is heated to a temperature above the thermal decomposition temperature in a stream of the inert gas at a temperature above the thermal decomposition temperature without pressurization.

6. The method for manufacturing a rare earth magnet according to claim 1, wherein the magnetic powder includes an insulating layer formed on its surface.

7. The method for producing a rare earth magnet according to claim 4, wherein the weight-average molecular weight of the binder compound is greater than 100,000 and less than or equal to 300,000.

8. The method for producing a rare earth magnet according to any one of claims 1 to 3, wherein the binder compound is an acrylic polymer.

Citation Information

Patent Citations

  • High resistance rare earth magnet and its manufacturing method

    JP2003022905A

  • Method of manufacturing r-t-b based rare earth magnet

    JP2010027852A

  • Rare earth magnet and method for manufacturing the same

    JP4784173B2